Willingness of farmers to participate in agri-environmental auctions in Finland - Grammatikopoulou, Ioanna; Iho, Antti; Pouta, Eija (Taylor & Francis, 2013)
Auctions have been applied in agri-environmental policy, serving as a key tool to overcome information asymmetries and generate important cost savings for governments. The efficiency of agri-environmental auctions depends on ensuring sufficient participation and avoiding a ‘learning by experience’ situation. In designing successful auctions, it is important to acknowledge farmer characteristics that might increase the adaptability of auctions and also recognize whether past experience affects future participation. This paper uses data from an auction experiment conducted in Nurmijärvi, Southern Finland. We account for socio-demographic, spatial and attitude variables and investigate their effect on the probability of past and future auction participation. Due to the small number of actual participants, we employ a relogit model to correct the coefficient estimates derived by a binary logit model. According to the analysis, large-scale farmers are more likely to have participated in the pilot auction, while older farmers, those engaged full time in farming and less well-trained farmers were less likely to be positive towards future auctions. Past participation was positively and significantly related to prospective auctions. Our findings suggest a strong relationship between attitudes and participation, particularly regarding specific environmental benefits attached to the auction scheme, novelty and financial features as well as the complexity of the auction mechanism. The predicted probability for both past and future participation elicited by the relogit model was consistent with the sample probability, and hence by applying a relogit to correct for rare-event bias we derived more reliable estimates.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; auction; attitude; relogit model; auctions; participation; attitudes; statistical methods; huutokauppa; osallistuminen; asenteet; tilastolliset mallit